Panic Buying, Trust Issue, Impulse Buying on Purchase Intensity on the Shopee Marketplace During the Covid-19 Pandemic: Panic Buying, Trust Issue, Impulse Buying terhadap Intensitas Pembelian pada Marketplace Shopee Selama Pandemi Covid-19 - Hidayah, Nur; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2023)
This study aims to explain the variables of panic buying, trust issue s, impulse buying on purchasing intensity either partially or simultaneously. The method used in this research is descriptive quantitative method. By distributing questionnaires to shopee application users at Muhammadiyah University of Sidoarjo as a data collection technique. The total sample used in this study was 130 respondents. The data analysis technique used is multiple linear regression. The sampling technique used the accidental sampling method, namely by distributing questionnaires to respondents who were accidentally encountered. The results of this study indicate that partially panic buying has an effect on purchase intensity, partially trust issue affects purchase intensity, impulse buying partially affects purchase intensity and for panic buying, trust issue , and impulse buying variables have a simultaneous effect on purchase intensity.